2018
DOI: 10.3892/ijmm.2018.3978
|View full text |Cite
|
Sign up to set email alerts
|

C1QTNF6 is overexpressed in gastric carcinoma and contributes to the proliferation and migration of gastric carcinoma cells

Abstract: In the present study, proteins differentially expressed between gastric cancer tissue and para-tumoral normal gastric tissues were screened, and the function of the highly expressed protein c1QTNF6 in gastric carcinoma was investigated. The differential expression of mRNAs extracted from the tumor and adjacent tissues was analyzed using Genechip assay. An AGS si-c1QTNF6 cell line was constructed using shRNA-c1QTNF6 lentivirus. The cell invasion and migration ability of c1QTNF6-knockdown cells were determined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 30 publications
(33 reference statements)
2
31
0
Order By: Relevance
“…38 A study found that C1QTNF6 was upregulated in gastric carcinoma and contributed to the migration and proliferation of gastric carcinoma cells. 39 Study showed that targeting twist family bHLH transcription factor 1 (TWIST1) through loss of function can inhibit the tumorigenicity of glioblastoma. 40 High hexokinase 3 (HK3) expression was associated with epithelialmesenchymal transition (EMT) in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…38 A study found that C1QTNF6 was upregulated in gastric carcinoma and contributed to the migration and proliferation of gastric carcinoma cells. 39 Study showed that targeting twist family bHLH transcription factor 1 (TWIST1) through loss of function can inhibit the tumorigenicity of glioblastoma. 40 High hexokinase 3 (HK3) expression was associated with epithelialmesenchymal transition (EMT) in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…C1qTNF6 [C1qTNF-related protein 6, also designated CTRP6 (C1qTNF-related protein-6)] is a glycoprotein composed of 259 amino acids and has a unique molecular structure, consisting of four domains (signal peptide, short N-terminal variable region, collagen domain and C-terminal C1q domain) [8,9]. It expresses mainly in adipose tissue, lung, stomach and so on [10][11][12]. Growing body of evidences suggest that C1QTNF6 regulates cardiac fibrosis, inflammatory reaction, endothelial cell function, fibrogenesis, fatty acid metabolism and carcinogenesis , and so on [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…It is expressed mainly in placenta, and also in heart, adipose tissue, and uterus . Studies have shown that it is involved in cell proliferation and differentiation, apoptosis, lipolysis and adipogenesis, insulin sensitivity, fibrogenesis, inflammation, embryogenesis, and tumorigenesis . Recently, it was identified in ovarian cells, indicating a possible role in modulating reproductive system function .…”
Section: Introductionmentioning
confidence: 99%